Describing Peripancreatic Collections According to the Revised Atlanta Classification of Acute Pancreatitis: An International Interobserver Agreement Study. Issue 7 (August 2017) - Bouwense, Stefan A.; van Brunschot, Sandra; van Santvoort, Hjalmar C.; Besselink, Marc G.; Bollen, Thomas L.; Bakker, Olaf J.; Banks, Peter A.; Boermeester, Marja A.; Cappendijk, Vincent C.; Carter, Ross; Charnley, Richard; van Eijck, Casper H.; et al.
Abstract : Objectives: Severe acute pancreatitis is associated with peripancreatic morphologic changes as seen on imaging. Uniform communication regarding these morphologic findings is crucial for accurate diagnosis and treatment. For the original 1992 Atlanta classification, interobserver agreement is poor. We hypothesized that for the revised Atlanta classification, interobserver agreement will be better. Methods: An international, interobserver agreement study was performed among expert and nonexpert radiologists (n = 14), surgeons (n = 15), and gastroenterologists (n = 8). Representative computed tomographies of all stages of acute pancreatitis were selected from 55 patients and were assessed according to the revised Atlanta classification. The interobserver agreement was calculated among all reviewers and subgroups, that is, expert and nonexpert reviewers; interobserver agreement was defined as poor (⩽0.20), fair (0.21–0.40), moderate (0.41–0.60), good (0.61–0.80), or very good (0.81–1.00). Results: Interobserver agreement among all reviewers was good (0.75 [standard deviation, 0.21]) for describing the type of acute pancreatitis and good (0.62 [standard deviation, 0.19]) for the type of peripancreatic collection. Expert radiologists showed the best and nonexpert clinicians the lowest interobserver agreement. Conclusions: Interobserver agreement was good for the revised Atlanta classification, supporting the importance for widespread adaption of this revised classification for clinical and research communications. Abstract : Supplemental digital content is available in the text.